Magnitude and direction of elbow torque asymmetries in manual wheelchair users - Biduski, Grazieli Maria; Knihs, Débora Aparecida; Nery de Oliveira, Silas; Hoinaski, Laís Peixoto; Rossato, Mateus; Freitas, Cíntia De La Rocha (Frontiers in Sports and Active Living, 2023)
The aims of the present study are to investigate the magnitude and direction of the elbow torque asymmetries in manual wheelchair users and to verify the agreement levels of the asymmetry's direction between different velocities and contraction modes in the isokinetic test. The sample was composed of 14 manual wheelchair users (four women, 10 men). The peak torque of the elbow flexors and extensors were measured on the dominant and non-dominant limbs, using a set of concentric/eccentric contractions at speeds of 60° s−1 and 180° s−1. Asymmetries were calculated by a specific equation, and the levels of agreement of the asymmetry's direction were calculated using Kappa coefficient. The main results showed a large variability in the magnitude of the asymmetries, ranging from −73.1% (ND) to 59.9% (D) between participants. The agreement levels of the elbow flexors and extensors between the different contraction modes were great (k = 0.71–0.85) for most of the velocities [except for flexors of 60° s−1 (k = 0.29)], but the agreement levels were only slight to fair (k = 0.16–0.31) for most of the contraction modes when comparing between velocities [except for flexors eccentric (k = 0.71)]. In conclusion, the elbow torque asymmetries are highly variable between subjects in terms of magnitude. In addition, in general, the limb favored by the asymmetry is the same when comparing between velocities, but not when comparing between contraction modes.